Socialization of Business Identification Number Towards MSME’s Sustainability in Tambakrejo Urban Village, Gayamsari Subdistrict, Semarang City - Fitra Islamy, Ilma Maulana; Widhiastuti, Anita Indah (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2023)
In fact, it turns out that MSME actors in Tambakrejo Village, Gayamsari District, Semarang City have experienced developments from time to time. As a state of law, in this case, legality efforts and legal protection by the government are needed for MSME actors. So far, MSMEs in Temabakrejo sub-district still lack knowledge about the mechanism of making a Business Registration Number (NIB) using Single Submission (OS). Therefore, this community service activity has the aim of helping the people of Tambakrejo Village in solving this problem. Socialization efforts, assistance, and direction in making NIB have been made to the community through OSS, where it is hoped that later the community will have new knowledge and understanding related to the protection of MSMEs that they have pioneered. In its implementation, there are 3 stages used, namely by socializing efforts to the community regarding the importance of making NIB, training in making NIB with OSS, and continuing with efforts to assist the community in making the NIB. The implementation of this activity has increased the knowledge and understanding of the community in TAmbakrejo Village, Gayamasari District, Semarang City